Práticas discursivas e subjetivação do sujeito evadido do curso de matemática da Universidade Estadual de Maringá - Ferreira, Luciano (2016)
This research had as its objective to write the discourse regarding the dropout subject of the mathematics graduation course at Universidade Estadual de Maringá (UEM), according to Michel Foucault s theory, through the dropout students own utterances. The objective, besides that of verifying dropout students representations, is to incite a critical discussion regarding their representations on dropping-out. The way in which the former student inserts himself in the dropout subject discourse was described. With this study, we seek as well to give voice to the excluded subjects, which so far had been nothing more than statistic tables in the University. In order to achieve that, we observed the subject s objectivation in the official documents of UEM. We carried out a survey on the drop-out rates registered in the mathematics course between the years of 2003 and 2013, which are of approximately 50%. We assessed what the legislation prescribes for the mathematics graduation course, the political-pedagogical projects (PPP), the course and its academic staff records. In search of the dropout student s objectivation process, we delimited the analysis to the archive referring to the drop-out object. The study of scientific papers and related documents provided subsidies for the elaboration and analysis of the interviews carried out with 26 dropout academics, in the eleven years covered by this research. The materiality of the utterances in the interviews associated itself to the research field and to the discourses concerning the drop-out referential so that we could mark the subject position of those who have been through the mathematics course and have not graduated. Due to our foucaultian discourse analysis basis, the following concepts were highlighted: utterance, discursive practice, subjectivation and objectivation processes, all of which allows the individual to become, in the quality of a subject, knowledge object. The analysis has shown that there is institutional knowledge which objectifies these mathematics course ex-students, such as: void of prerequisites, deprived of time for studying, lacking on sufficient intelligence and interest. Nevertheless, the dropout subjects assume only a few of the mentioned practices which have already spoken of who they are, and reject others. They resist the subject position the Institution provided them with by discursivizing themselves as one who is able to obtain other university degrees or even a mathematics degree in some other institution or modality, ceasing to be mere data on paper, becoming a discourse subject.